Advanced Nanoscale Build‐Up Sensors for Daily Life Monitoring of Diabetics. Issue 15 (8th July 2020) - El‐Safty, Sherif A.; Shenashen, Mohamed A.
Abstract: High‐throughput screening, early diagnosis, prognosis, daily routine, and real‐time monitoring are the main factors in diabetes management. Novel nanodynamic sensory designs can support these processes by offering i) a great diversity of periodic glucose sensing assays, ii) multiple and large‐scale autosampling assessments of glucose levels, and iii) possible glucose analysis by using a small sample size. This work highlights the nano, biosensor design engineering rationales used to explore a wide range of glucose levels and transduce them into readable output signals for dead‐end and fast‐response analyses. Powerful nanoscale chemical sensor designs can be used as alternatives to traditional assessment and analytical methods in the laboratory and integrated into robotics, smartphones, or wearable devices. These innovations would offer the future steady progress required for biotechnological, analytical, and sensing applications with less time consumption and simple operation. A new generation of nano, bioglucose sensor designs featuring platforms with nanometric dimensions, geometries, surface functionality, and physical/chemical properties is also attractive as a candidate for developing diabetic sensing devices. Indeed, the developed fabrication of diabetic nanosensor devices with compact size miniaturization, autosampling analysis and collection, in situ controlling assays, and defined signaling read‐out detection is urgently needed to avoid a risk associated with diabetes. Abstract : The nanoscale sensor is one of the most reliable cornerstones for nanofuture diabetes devices. The nano, biosensor glucose designs with readable output signals and rapid response analyses offer alternatives to traditional detection techniques. Integrating wearable sensor devices into robots and smartphones is a future of diabetic monitoring.